Updated programmatic learning outcomes for the training of family physicians in South Africa - Robert Mash; Hannes Steinberg; Mergan Naidoo (South African Family Practice)
The training of medical specialists should constantly be re-aligned to the needs of the population and the health system. The national Education and Training Committee of the South African Academy of Family Physicians reached consensus on the updated programmatic learning outcomes for the training of specialist family physicians in South Africa. Learning outcomes were first developed to guide training programmes when the speciality was recognised in 2007. Fifteen years later, it was time to revisit and revise these learning outcomes. Learning outcomes define what family physicians are able to do at the end of 4 years of postgraduate training. This revision presents five unit standards and 83 programmatic exit-level learning outcomes.